Radical Green Political Theory and Land Use Decision Making for Sustainability in the Region of Waterloo, Ontario, Canada - Markvart, Tanya (Environnement Urbain / Urban Environment, 2009)
AbstractRadical green political theory outlines some fundamentals for a sustainable society; if and how they might be translated into practice has become a matter of much discussion. This study investigates the role that radical green political theory might play in land use decision making for sustainability. Land use decision making criteria are derived from Dobson’s (2000) portrayal of ecologism and evaluated against Gibson et al.’s (2005) core decision making criteria for sustainability. Strengths and limitations of a revised set of criteria are investigated by applying them to the particulars of the Waterloo Moraine land use case in Waterloo, Ontario, Canada.